Open caption Telop as a teaching tool in Japanese language classroom / Kamarul Azam Kamarul Azmi - Kamarul Azam , Kamarul Azmi (2024)
One of the biggest challenges in teaching a foreign language (FL) during a pandemic is providing a natural setting for learners to practise the target language. Alternatively, scholars have found that presenting videos with captions can enhance various language skills and improve the viewing experience for FL learners. To date, numerous studies on captioned video for FL teaching have been conducted for European languages, especially English, where normal captions are used. This raises the question of whether captions in other languages, particularly Japanese, can bring the same effect as English captions. This study involved eight undergraduate students from the Universiti Malaya who majored in Japanese. Participants were recruited to join an 8-week course called ‘Learning Japanese via Telop’. During the course, participants were taught using a distinctive Japanese caption called telop, and several assignments were given, including vocabulary recognition tests, video comprehension tests, video analysis sheets, and learning diaries as in-class and at-home assignments. The findings of this study demonstrated that the multiple functions and attributes of telop can help instructors facilitate Japanese language teachings, such as enhancing understanding of meaning, pronunciation, and grammar, as well as cultural learning such as lifestyle and attitude. Participants reported that telop helped them understand Japanese better, enhanced their learning experiences, and promoted language practice. The study also highlighted several factors, such as criteria for video selection, technical issues, and pedagogy, that influenced the success of using telop as a teaching tool. Overall, this study suggests that Japanese language instructors should consider using telop as a teaching tool as an alternative way to expose Japanese language learners to a natural setting of the Japanese language. The study also recommends that future research may use mixed method, using instruments such as questionnaires and tests, to measure the effect of telop on learners’ perceptions and actual learning outcomes.